2020
DOI: 10.1097/md.0000000000022834
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of combination therapy with alpha-blockers and phosphodiesterase-5 inhibitors compared with monotherapy for lower urinary tract symptoms

Abstract: Purpose: This study aimed to compare the efficacy and safety of combination therapy consisting of α-blockers and different phosphodiesterase type 5 inhibitors for lower urinary tract symptoms (LUTS) by performing a network meta-analysis. Method: Relevant articles were retrieved from the Cochrane Library, PubMed, and EMBASE databases. Bayesian network meta-analyses were performed with a random-effect model to compare the efficacy and safety of combination therapy with α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Tadalafil by itself has been shown to lower IPSS total score, voiding subscore, and storage subscore in men ≥ 40 years [ 14 ]. Several studies have shown that combination therapy of PDE5I’s and alpha blockers work better than either drug alone in managing LUTS due to BPH [ 15 , 16 ]. The order of drug administration does not have any significant effects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil by itself has been shown to lower IPSS total score, voiding subscore, and storage subscore in men ≥ 40 years [ 14 ]. Several studies have shown that combination therapy of PDE5I’s and alpha blockers work better than either drug alone in managing LUTS due to BPH [ 15 , 16 ]. The order of drug administration does not have any significant effects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, vardenafil and alpha blockers ranked higher than sildenafil and tadalafil combinations. Importantly, this combination was found to be more effective at improving LUTS compared to alpha-blockers alone [ 18 ]. Several trials have been conducted to assess the use of antimuscarinics in BPH as either single-line monotherapy or combination therapy with an alpha blocker such as terazosin.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown that combination therapy with PDE5 is and alpha-blockers provided better outcomes than a-adrenergic blocker monotherapy. 4 Several metaanalyses have defined the efficacy and safety of PDE5 is alone or in combination with α1-blockers for the treatment of BPH-LUTS. Moreover, the combination therapy can significantly improve international prostate symptom score (IPSS) and maximal flow rate (Qmax).…”
Section: Effectiveness Of Tadalafil and Tamsulosin Combination In Ben...mentioning
confidence: 99%